Political prisoners in the Fatimid state (358-427 AH/969-1035 AD) - Sabreen Kareem Abd, Asst.Lect. (lark, 2026)
The Fatimid state is one of the most prominent Islamic states, leaving a profound impact on the course of Islamic political and cultural history. It was distinguished by its political power, advanced administrative organization, and remarkable economic and intellectual prosperity. Its caliphs descended from Lady Fatima al-Zahra (peace be upon her). Its founding was linked to the Ismaili movement, which embraced the principle of the Imamate of Ismail, son of Imam Ja'far al-Sadiq (peace be upon him). The Fatimids were able to establish their state in the Maghreb. Their state was distinguished by its longevity and the efficiency of its administrative institutions compared to contemporary states.  During its heyday, the Fatimid state witnessed a vast geographic expansion, encompassing Egypt, the Levant, and North Africa, including the Maghreb, Sicily, Yemen, and the Hejaz. This expansion was accompanied by a remarkable economic boom and a significant intellectual movement, facilitated by the Fatimid caliphs' support for science and scholars, making their state a beacon of knowledge and culture. Fatimid rule lasted for approximately two hundred and sixty years, during which fourteen caliphs succeeded one another, beginning with Abdullah al-Mahdi and ending with al-Adid li-Din Allah.Amid the political turmoil witnessed by the Fatimid state, the issue of political prisoners emerged as a multi-dimensional phenomenon. Their role was not limited to being a result of political conflict, but rather transformed into effective tools in the realms of politics and diplomacy. Political prisoners were used as a means of negotiation and political pressure with both internal and external powers.These prisoners were often held under special circumstances that varied depending on their social and political status. High-ranking figures were treated with kindness, while others were released in exchange for a ransom or as part of political settlements aimed at achieving strategic gains for the Fatimid state.The impact of political prisoners was not limited to foreign relations; it also extended to within the state itself, as some prisoners served as a bargaining chip on political decision-makers and were sometimes exploited to influence domestic policy…Our research,(Political Prisoners in the Fatimid State (358-427 AH/969-1035 AD)), sheds light on the most prominent political figures captured during the Fatimid period.
Keywords: Keywords: Judgment, decision, prisoners, system, authority.